NASA's master plan. - O'Keefe, S. (IEEE spectrum)
This paper describes how the author's leadership team was asked to help identify NASA's core strengths and activities and think hard about how each of them supports their mission. The purpose of the exercise is focus-and also direction. If a program or activity doesn't support one of NASA's three key objectives, one has to ask why one is doing it, even if one may be doing it rather well. Once one has focused on the activities that do fit into NASA's mission, one must make sure one is managing them in the best way possible. The first task is to examine what NASA is doing and why it is doing it.